Brand first? The effect of hotel online word-of-mouth on consumer brand sensitivity - Li, Xianchun; Fan, Yiying; Zhong, Xin; Hu, Jiajing (Frontiers in Psychology, 2022)
With the e-commerce development and changing of hotels’ booking channels, the online word-of-mouth, as a new signal of quality, is becoming to attract more attention of consumers. Using the scenario experiment, this study explores the effect of online word-of-mouth on brand sensitivity of consumers during the decision making for hotel booking. The results show that if the information about hotels obtained is limited in the decision-making process, consumers would have a higher sensitivity to the hotel brand. Increasing information about the online word-of-mouth can effectively reduce consumers’ brand sensitivity to hotels. Besides, the moderating effect of the hotel grade on the relationship between the online word-of-mouth and brand sensitivity is affected by the scale of the negative differences of word-of-mouth.